Effects of different concentrations of biochar amendments and Pb toxicity on rhizosphere soil characteristics and bacterial community of red clover (Trifolium pretense L.) - Meng, Lingdong; Wu, Yuchen; Mu, Meiqi; Wang, Zicheng; Chen, Zirui; Wang, Lina; Ma, Zewang; Cui, Guowen; Yin, Xiujie (Frontiers in Plant Science, 2023)
Amending soil with biochar can reduce the toxic effects of heavy metals (HMs) on plants and the soil. However, the effects of different concentrations of biochar on the properties and microbial activities in lead (Pb)-contaminated soils are unclear. In this study, two Pb concentrations were set (low, 1000 mg/kg; high, 5000 mg/kg), and five corn straw biochar (CSB) concentrations (0, 2.5, 5, 10 and 15%) were used to determine the response of the growth and rhizosphere of T. pratense (in terms of soil properties and bacteria) to CSB and Pb application. The results showed that 5% CSB better alleviated the toxicity of Pb on the shoot length of T. pratense, the biomass increased by 74.55 and 197.76 % respectively and reduced the enrichment factor (BCF) and transport factor (TF) of T. pratense. Pb toxicity reduced soil nutrients, catalase (CAT), acid phosphatase (ACP) and urease activity, while the addition of CSB increased soil pH, soil organic matter (SOM) content and soil enzyme activity. 16S rDNA amplicon sequencing analysis showed that Pb toxicity reduced the diversity of rhizosphere bacteria in T. pratense and reduced the relative abundance of plant growth-promoting rhizobacteria such as Gemmatimonas, Devosia and Bryobacter. Spearman correlation analysis showed that the addition of alkaline CSB restored the relative abundance of rhizobacteria positively correlated with pH, such as Chitinophaga, Sphingomonas, Devosia and Pseudomonas, and thus restored the rhizosphere soil environment. The results of this study provide a basis for the restoration of Pb-contaminated soil by biochar and provide a reference for the subsequent use of beneficial bacteria to regulate the remediation efficiency of T. pratense.